Sustainability reporting and greenwashing: a bibliometrics assessment in G7 and non-G7 nations - Sheela Sundarasen; Beata Zyznarska-Dworczak; Sanjay Goel (Cogent Business & Management, 2024)
This study aims to provide a comprehensive overview of the scholarly work and discussion on greenwashing in sustainability reporting (GiSR) and tease out dominant themes that emerge from the literature, and the different emphasis of research between G7 and non-G7 nations. Based on a total of 87 articles from the Web of Science (WoS) database, this study adopts the bibliometrics and content analysis approach, which uses both numerical and visualization techniques to examine the extant literature from 2003 – 2022. The outcomes of the scientific bibliographic coupling identified three dominant themes: (i) Greenwashing (exaggeration of green effort); (ii) ESG disclosures and performance gap and (iii); Communicative legitimation strategies and reporting of negative aspects. Results highlighted overlaps and differences between G7 and non-G7 countries, and the need for further research in non-G7 countries on the institutional, cultural, and socioeconomic variances on greenwashing, firm-level variations in behavior, leadership and strategy on greenwashing, the use of technology in detecting greenwashing, as well as the role of regulatory and governance in corporate reporting to mitigate greenwashing. This study hopes to attract the attention of researchers, policymakers, and businesses to counteract greenwashing by recognizing its determinants and contribute to the quality and credibility of sustainability reporting.
Keywords: 650; Greenwashing; sustainability/corporate reporting; ESG; disclosure; bibliometric analysis; G7 countries; non-G7 countries